PERAN SATUAN POLISI PAMONG PRAJA DALAM MENANGANI PEKERJA SEKS KOMERSIAL (PSK) DI KABUPATEN LEBAK - Erna Nuraena; Ade Hadiono (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2021)
This research is intended to find out how pamong praja police unit's role in dealing with Commercial Sex Workers in accordance with Regional Regulation of Lebak District No. 17 of 2006 on The Implementation of Order, Hygiene and Beauty (K3), and to know the obstacles or obstacles faced by pamong praja police unit officers in dealing with Commercial Sex Workers (PSK) in Lebak Regency. The method used in this study is a qualitative method, with the number of informants as many as 12 people, with details of 4 Satpol PP, 1 Police person, 3 People Community and 4 Commercial Sex Workers (PSK). From the results of this study can be concluded that Pamong Praja Police officers of Lebak Regency rarely conduct raids on a regular basis, tend to be helped a lot by lebak resort police. Every time there will be an operation of information always leaked, Satpol PP officers treat the PSK who are caught within the limits of fairness, advise the psk to leave their dirty work, and for the PSK who is caught repeatedly sent to the social home to be fostered by the relevant service. From social service data obtained information only about 35% of the students who have followed the coaching conscious and left the world at night, while the rest of the people who return to the work for various classic reasons, the main of which is economic difficulty and want to quickly earn money. Based on the facts in the field, the mushrooming of new psk who are young and have regular customers who are young is also certainly a concern of all of us so that the younger generation of this nation is not morally damaged. Surely the role of Satpol PP as the vanguard in running the government number 17 year 2006 must remain firmly acted.